If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + -7b = -7(b + 2) Reorder the terms: -11 + -7b = -7(2 + b) -11 + -7b = (2 * -7 + b * -7) -11 + -7b = (-14 + -7b) Add '7b' to each side of the equation. -11 + -7b + 7b = -14 + -7b + 7b Combine like terms: -7b + 7b = 0 -11 + 0 = -14 + -7b + 7b -11 = -14 + -7b + 7b Combine like terms: -7b + 7b = 0 -11 = -14 + 0 -11 = -14 Solving -11 = -14 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -4(a-3)-(a+6)=1-8a+5+7a | | (3x-4)(2x+11)=0 | | -8+3-6x+6=-7x-2 | | 9x^2-17x-30= | | -8=-2+3/4x | | -3(4y-8)=-36 | | 30+5x+6x=30x | | 2x^4-128x=0 | | 351=3b | | 0.19y+0.05(y+7000)=2030 | | 3(-7a+6)-6a=-2a+18 | | Ax+r=5 | | 325-m=1500+2(m-500) | | 11x+8-30-x=-2(2x+4)-3(2x-2) | | 9y-3=19-24 | | -134=5(1+3x)-4 | | a+x=y+z | | 10-2.7y=y | | 3x-5(x-2)=-6+4x+4 | | 2x^5-6x^4-216x^3=0 | | -2(5x-4)=22 | | x-13=23-2x | | -3(x-2)-1=5(x+3)+38 | | g(x)=-2x+5 | | 5.9x-4.9x^2=0 | | 9+(9+.5x)=x | | 11+7q=15+6q | | -(2x-5)=12 | | -(n-4)+3(n-2)=2 | | y^2+25=1oy | | 2(5q-7)=3q | | -3(k-5)=-6(1+4k) |